Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.1 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 764: 38


$x=(1-\sqrt 3, 1+\sqrt 3)$

Work Step by Step

Step-1 : Add $2$ from both sides of the equation $x^2-2x=2$ Step -2 : Add the square of half of the co-efficient of $x$ to both sides. Co-efficient of $x =-2$ Half of $-2 = \frac{1}{2}×-2=-1$ Square of $-1$ is $-1×-1=1$ The equation becomes $x^2-2x+1=2+1$ Step-3 Factor the trinomial and simplify the right hand side. $(x-1)^2=3$ Step-4 Use the square root property and solve for $x$ $(x-1)=±\sqrt 3$ Step-5 Add 1 on both the sides $x=1±\sqrt 3$ Therefore the solution set is $(1-\sqrt 3, 1+\sqrt 3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.